A new analysis of Galileo dust data near Jupiter. (May 2015) - Soja, R.H.; Hamilton, D.P.; Altobelli, N.
Abstract: The Galileo Dust Detection System (DDS) detected a population of micron-sized grains in and amongst the orbits of Io, Europa, Ganymede and Callisto. Previous studies, using roughly 50% of the data now available, concluded that the dominant sources for the impacts were magnetospherically captured interplanetary particles largely on retrograde orbits (Colwell et al., 1998b; Thiessenhusen et al., 2000 ) and impact-generated ejecta from the Galilean satellites (Krüger et al., 1999b; Krivov et al., 2002a ). Here we revisit the problem with the full data set and broaden our consideration to include four additional source populations: debris from the outer satellites, interplanetary and interstellar grains and particles accelerated outwards from Io and the jovian rings. We develop a model of detectable orbits at each Galileo position and we find that about 10% of the impact data require non-circular orbits with eccentricities greater than 0.1. In addition, ~3% of impacts require orbital solutions with eccentricities in excess of 0.7. Using the spatial distribution of particles, we are able to exclude, as dominant sources, all the additional source populations except for outer satellite particles. A study of DDS directional information demonstrates that none of the six standard sources fit the data well and thus a combination of sources is necessary. There are insufficient data to uniquely identify the relative strengths of the various contributions. However, we find an excess of large particles that is consistent with retrograde trajectories. Abstract : Highlights: We analyse dust populations in the Jovian system with the full Galileo DDS dataset. A combination of source populations is required to explain the data. About 10% of the dataset require non-circular orbits. We find an excess of large particles consistent with retrograde orbits.